2016
DOI: 10.1371/journal.pone.0165346
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Blood Stream Infection due to Candida Species in a Tertiary Care Hospital in Japan over 12 Years: Importance of Peripheral Line-Associated Candidemia

Abstract: BackgroundCandidemia is an important cause of mortality in healthcare settings. Peripheral lines are a source of candidemia, yet few studies have reported on the clinico-epidemiological features of candidemia due to peripheral-line associated blood stream infection (PLABSI).MethodsWe conducted a single-centre retrospective cohort study of all patients with candidemia between 2002 and 2013. PLABSI was defined as the presence of at least one of the following: the presence of phlebitis or the resolution of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…The mean annual incidence in the whole hospital was 1.48 per 10 000 PD and was similar to incidences found in tertiary care hospitals from other developed countries including Canada, Japan and Spain and to the one reported in the same hospital during the period 2001‐2005 (1.51 per 10 000 PD) . The low mean annual incidence (0.59 episodes per 10 000 PD) in the neonatal unit is consistent with the decreasing trend in candidaemia incidence in this unit worldwide .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The mean annual incidence in the whole hospital was 1.48 per 10 000 PD and was similar to incidences found in tertiary care hospitals from other developed countries including Canada, Japan and Spain and to the one reported in the same hospital during the period 2001‐2005 (1.51 per 10 000 PD) . The low mean annual incidence (0.59 episodes per 10 000 PD) in the neonatal unit is consistent with the decreasing trend in candidaemia incidence in this unit worldwide .…”
Section: Discussionsupporting
confidence: 85%
“…(1.51 per 10 000 PD). 11,19,24,27,31 The low mean annual incidence (0.59 episodes per 10 000 PD) in the neonatal unit is consistent with the decreasing trend in candidaemia incidence in this unit worldwide. 32 However, the incidence of candidaemia increased significantly between 2004 and 2015 in the other ICUs and drove the increasing incidence of the whole hospital.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the present study, the overall incidence of candidemia was 0.056 cases/1000 hospital admissions, which was lower than that of previous studies in Japan (1.74/1000 hospital admissions). 20 Previous studies reported the incidence of candidemia in the US (0.16–0.33/1000 hospital admissions) and in European countries (0.92–1.5/1000 hospital admissions). 21 23 The incidence noted in the present study was similar to that in Finland (0.026–0.03/1000 hospital admissions).…”
Section: Discussionmentioning
confidence: 99%
“…In the past study [17], we reported that peripheral-line associated candidemia (PLAC) was an important cause of candidemia in the healthcare settings. Although IDC was associated with the predictors of PLAC, we did not evaluate the survival outcome of IDC on candidemia [17].…”
Section: Introductionmentioning
confidence: 99%